Electoral Cycles, Partisan Effects and U.S. Naturalization Policies - Marcus Drometer; Romuald Méango (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2017)
Using a panel of naturalizations in U.S. states from 1965 to 2012, we empirically analyze the impact of elections on naturalization policy. Our results indicate that naturalization policy is (partly) driven by national elections: there are more naturalizations in presidential election years and during the terms of Democratic incumbents. We then investigate the dynamics of an incumbent's behavior over the course of the his term in detail, finding that the effects are more pronounced in politically contested states and for immigrants originating from Latin America.
Keywords: H11; D72; F22; 330; Electoral cycles; naturalization policy